2015
DOI: 10.1371/journal.pone.0139709
|View full text |Cite
|
Sign up to set email alerts
|

Combined Treatment with Exendin-4 and Metformin Attenuates Prostate Cancer Growth

Abstract: IntroductionRecently, the pleiotropic benefits of incretin-based therapy have been reported. We have previously reported that Exendin–4, a glucagon-like peptide–1 (GLP–1) receptor agonist, attenuates prostate cancer growth. Metformin is known for its anti-cancer effect. Here, we examined the anti-cancer effect of Exendin–4 and metformin using a prostate cancer model.MethodsProstate cancer cells were treated with Exendin–4 and/or metformin. Cell proliferation was quantified by growth curves and 5-bromo–2′-deoxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 37 publications
2
39
1
Order By: Relevance
“…Particularly, it was observed that GLP‐1R expression in human PC tissue and PC cell lines and Ex‐4 attenuated PC growth both in vitro and in vivo via the inhibition of extracellular signal‐regulated kinase–mitogen‐activated protein kinase activation, leading to the inhibition of cell proliferation (Figure ) . The authors’ further study revealed that both Ex‐4 and metformin significantly decreased PC cell proliferation, as shown by the decrease of Ki67 expression . In this study, metformin, but not Ex‐4, induced apoptosis in the LNCaP cells through the activation of 5′ adenosine monophosphate (AMP)‐activated protein kinase (Figure ).…”
Section: Drugs For Type 2 Diabetes Mellitus and Prostate Cancermentioning
confidence: 58%
See 2 more Smart Citations
“…Particularly, it was observed that GLP‐1R expression in human PC tissue and PC cell lines and Ex‐4 attenuated PC growth both in vitro and in vivo via the inhibition of extracellular signal‐regulated kinase–mitogen‐activated protein kinase activation, leading to the inhibition of cell proliferation (Figure ) . The authors’ further study revealed that both Ex‐4 and metformin significantly decreased PC cell proliferation, as shown by the decrease of Ki67 expression . In this study, metformin, but not Ex‐4, induced apoptosis in the LNCaP cells through the activation of 5′ adenosine monophosphate (AMP)‐activated protein kinase (Figure ).…”
Section: Drugs For Type 2 Diabetes Mellitus and Prostate Cancermentioning
confidence: 58%
“…61 The authors' further study revealed that both Ex-4 and metformin significantly decreased PC cell proliferation, as shown by the decrease of Ki67 expression. 62 In this study, metformin, but not Ex-4, induced apoptosis in the LNCaP cells through the activation of 5′ adenosine monophosphate (AMP)-activated protein kinase ( Figure 2).…”
Section: Dase-4 Inhibitors and Glucagon-like Peptide (Glp)-1 Receptormentioning
confidence: 63%
See 1 more Smart Citation
“…Metformin, a potential anticancer agent, has been shown to inhibit growth and induce apoptosis though AMPK-dependent and -independent signaling pathways in CRPC cells5556. One study found that combination of metformin with other therapeutic agents, such as anti-AR agent bicalutamide, enhanced the growth inhibition of CRPC via AR-mediated signaling57.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this, we next examined the anti-prostate cancer effect of combined treatment with exendin-4 and metformin [72]. Exendin-4 and metformin additively decreased the growth rate, but not migration, of prostate cancer cells.…”
Section: Anti-prostate Cancer Effect Of Glp-1 Receptor Agonistmentioning
confidence: 99%